2016
DOI: 10.4103/0973-1296.186348
|View full text |Cite
|
Sign up to set email alerts
|

New phytochemical constituent and bioactivities ofHorwoodia dicksoniaeandRumex cyprius

Abstract: Background:Many plants growing in Saudi Arabia are used in folk medicine for treatment of several diseases.Objective:Information of the chemical constituents and biological activities of plants is desirable for the discovery of therapeutic agents and discovering the actual value of folkloric remedies.Materials and Methods:The compounds were isolated and purified using silica gel column chromatography and preparative high-performance liquid chromatography-diode array detector (HPLC-DAD) Method. The alcoholic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
7
1
Order By: Relevance
“…Also, Wang et al [33] found that with the significant antioxidant activities exhibited by shikonin, it has shown also a powerful cytotoxic activity with IC 50 equal to 0.83 and 0.53 (μg/mL), respectively, for the two cell lines MCF-7 and HCT-116. Furthermore, these results of R. roseus extracts were higher than those found by other studies done on plants of the same family (Polygonaceae); they showed that the extract from the species Rumex crispus, for example, had no cytotoxic activity (0%) against the MCF-7 cell line [34] and in others as well (Polygonum equisetiforme); a low activity against both MCF-7 and HCT-116 was found, with 11.3 and 14.5%, respectively [35].…”
Section: Cytotoxic Activitycontrasting
confidence: 65%
“…Also, Wang et al [33] found that with the significant antioxidant activities exhibited by shikonin, it has shown also a powerful cytotoxic activity with IC 50 equal to 0.83 and 0.53 (μg/mL), respectively, for the two cell lines MCF-7 and HCT-116. Furthermore, these results of R. roseus extracts were higher than those found by other studies done on plants of the same family (Polygonaceae); they showed that the extract from the species Rumex crispus, for example, had no cytotoxic activity (0%) against the MCF-7 cell line [34] and in others as well (Polygonum equisetiforme); a low activity against both MCF-7 and HCT-116 was found, with 11.3 and 14.5%, respectively [35].…”
Section: Cytotoxic Activitycontrasting
confidence: 65%
“…In addition, for both cell lines, HCT-116 and MCF-7, the DCM extract revealed the highest cytotoxic potential with almost 69.2 and 77.2% of inhibition, respectively. This inhibition may be due to the presence of some phenolic compounds, which are known for their important cytotoxic activities, especially cardamonin with IC 50 equal to 8.1 and 8.6 µ g/mL, respectively, against the two cell lines (MCF-7 and HCT-116) [ 65 ]. Other studies suggested potent activity against cancer cells, including MCF-7 and HCT-116 cell lines, among which shikonin molecule (IC 50 = 0.83 and 0.53 ( μ g/ml)), respectively [ 66 ], which confirms our obtained results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, for both cell lines, HCT-116 and MCF-7, the DCM extract revealed the highest cytotoxic potential with almost 69.2 and 77.2% of inhibition, respectively. is inhibition may be due to the presence of some phenolic compounds, which are known for their important cytotoxic activities, especially cardamonin with IC 50 equal to 8.1 and 8.6 µg/mL, respectively, against the two cell lines (MCF-7 and HCT-116) [65].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…110 New studies of non-local species reveal the health promoting phytochemicals that they contain. 111 The structures of these compounds are shown in Figure 6.…”
Section: Plant Materials Preparation Extractionmentioning
confidence: 99%